2016
DOI: 10.1136/annrheumdis-2015-207670
|View full text |Cite
|
Sign up to set email alerts
|

Does a family history of RA influence the clinical presentation and treatment response in RA?

Abstract: Family history of RA did not modify the clinical presentation of RA or predict response to standard treatment with MTX or TNFi. Treatment response, particularly drug survival, may itself be familial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…Similarly, Alazmi et al (36) found no association between family history of SpA and 6 month BASDAI50 response in axial SpA patients in Canada. In RA, a related but less familial disease, family history was not associated with TNFi treatment outcome among Swedish patients (44). These findings are in line with ours, showing a lack of association of family history with both drug survival and treatment response.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, Alazmi et al (36) found no association between family history of SpA and 6 month BASDAI50 response in axial SpA patients in Canada. In RA, a related but less familial disease, family history was not associated with TNFi treatment outcome among Swedish patients (44). These findings are in line with ours, showing a lack of association of family history with both drug survival and treatment response.…”
Section: Discussionsupporting
confidence: 89%
“…The present study extends our previous findings in which we investigated familial aggregation of EULAR response to treatment with MTX in monotherapy and tumor necrosis factor inhibitors (TNFi) [ 11 ]. Due to small sample sizes, that study could not investigate familial aggregation within MTX-treated individuals, but found a significant familial component related to TNFi discontinuation after 12 months.…”
Section: Discussionsupporting
confidence: 83%
“…Few studies have studied treatment persistence as the outcome, which, in a treat-to-target paradigm should serve as a proxy for favorable tolerance and sustained treatment response. Using persistence as the outcome measure, a previous study from our group found that family history of RA, in itself , was unable to predict persistence to MTX in DMARD monotherapy at 3 and 6 months, though that study did not take family history of MTX treatment response into account [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we focused on FDR‐RA who are considered at high risk to develop RA themselves. In fact, the family history of RA is one of the strongest risk factors for RA and a strong independent predictor for RA onset: in first‐degree relatives, the increased risk is from twofold to fourfold (Frisell, Saevarsdottir, & Askling, ). The Study Group for Risk Factors for Rheumatoid Arthritis was recently established by the European League Against Rheumatism (EULAR) Committee in order to develop specific recommendations for terminology to be used when describing different phases of the disease when conducting clinical studies (Gerlag et al., ).…”
Section: Discussionmentioning
confidence: 99%